1998
DOI: 10.1046/j.1523-1755.1998.00811.x
|View full text |Cite
|
Sign up to set email alerts
|

Injection of low and iso-osmolar contrast medium decreases oxygen tension in the renal medulla

Abstract: The oxygen tension (PO2) in the renal cortex and outer renal medulla in 26 rats was studied by use of oxygen microelectrodes before and after injection of x-ray contrast media (CM). The CM, iopromide, ioxaglate and iotrolan were administrated intravenously in iodine equivalent doses (1,600 mg iodine/kg body wt). Ringer's solution was used as the control. In the outer medulla, all three CM induced a decrease in PO2: iopromide (N = 6) from 30 +/- 3 to 18 +/- 4 mm Hg; ioxaglate (N = 7) from 32 +/- 6 to 15 +/- 4 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
103
0
3

Year Published

1999
1999
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(112 citation statements)
references
References 29 publications
6
103
0
3
Order By: Relevance
“…In the already hypoxic outer medulla, Po 2 fell from 26 mmHg at baseline to mean levels as low as 9 mmHg. Liss et al (10) reported a comparable decline of medullary Po 2 from approximately 30 to 15 mmHg with the administration of ionic and nonionic lowosmolar radiocontrast agents, as well as iso-osmolar dyes. The intensification of medullary hypoxia by contrast agents has also been documented noninvasively in rats (11) and humans (12), using blood oxygen-level-dependent magnetic resonance imaging (MRI), detecting increased unsaturated hemoglobin concentration within the renal medulla over extended periods of time.…”
Section: Physiologic Medullary Hypoxia Aggravated By Radiocontrast Amentioning
confidence: 90%
See 1 more Smart Citation
“…In the already hypoxic outer medulla, Po 2 fell from 26 mmHg at baseline to mean levels as low as 9 mmHg. Liss et al (10) reported a comparable decline of medullary Po 2 from approximately 30 to 15 mmHg with the administration of ionic and nonionic lowosmolar radiocontrast agents, as well as iso-osmolar dyes. The intensification of medullary hypoxia by contrast agents has also been documented noninvasively in rats (11) and humans (12), using blood oxygen-level-dependent magnetic resonance imaging (MRI), detecting increased unsaturated hemoglobin concentration within the renal medulla over extended periods of time.…”
Section: Physiologic Medullary Hypoxia Aggravated By Radiocontrast Amentioning
confidence: 90%
“…All measurements represent parenchymal Po 2 determined in the outer medulla. For iothalamate, cortical measurements are shown as well (7,10). may represent reduced regional microcirculatory blood flow, as well as enhanced oxygen consumption, that may not be fully compensated even during increased regional oxygen delivery.…”
Section: Radiocontrast-induced Decrease In Renal Oxygen Supplymentioning
confidence: 99%
“…These include sepsis that induces renal vasoconstriction through the release of endothelin and the use of radiocontrast imaging dyes that increase oxygen consumption for solute reabsorption and reduce regional inner medullary blood flow. [54][55][56][57][58][59][60][61] More generalized reductions in blood flow represent another major cause of AKI. These can result from hemorrhage, decompensated liver cirrhosis, treatment with non-steroidal anti-inflammatory drugs, congestive heart failure, and renal artery occlusion or stenosis.…”
Section: Repeated Episodes Of Acute Kidney Injurymentioning
confidence: 99%
“…Iopromide was previously shown actually to increase RMBF in control rats, although it reduces RMBF in diabetic rats 23 ; however, a reduction in PO 2 by iopromide has also been reported. 24 Taken together, the experimental setting seems to be crucial for determining the ultimate effect of CM on RMBF and PO 2 . In this study, iopromide did not reduce PO 2 or RMBF, which may in part rely on our particular dehydration protocol: Our rats were not given water for 12 h before the experiment.…”
Section: Renal Circulation and Oxygenationmentioning
confidence: 99%